ANALYSIS OF THE EFFECT OF ORIGINAL REVENUE AND LOCAL GOVERNMENT EXPENDITURE ON ECONOMIC GROWTH IN PURBALINGGA REGENCY 2013-2023 (Economics Studies and Banking Journal (DEMAND), 2025)
This study examines the influence of Locally Generated Revenue (PAD) and Local Government Expenditure on economic growth in Purbalingga Regency, Indonesia, during the period 2013–2023. Using secondary time series data and an Error Correction Model (ECM) approach, the analysis is conducted to capture both short-term dynamics and long-term equilibrium relationships. The results show that PAD and government expenditure have no significant effect on economic growth in the long run, while in the short run both have a significant effect. A robust error correction mechanism indicates the ability of the regional economy to adjust towards long-term equilibrium. Although limited to fiscal variables, these findings emphasize the need to incorporate other factors such as investment, labor, inflation, and human development in future research. This study provides new evidence on the fiscal determinants of regional economic growth and offers insights for local governments in optimizing fiscal policies to promote sustainable development.